Study of the Crystallization of Nanoporous Mixed Metal Oxide Phases - Charis R. Theocharis; Christothea Attipa; Evroula Hapeshi; Aphrodite Tillirou; Rebecca Kokkinofta (Adsorption Science & Technology)
A systematic study of the synthesis and characterization of pristine ceria and of mixed cerium/metal oxides has been undertaken. Various synthetic routes were explored, with the crystallization process being examined via thermal analysis, XRD and electron microscopy. It was shown that even when multiple phases were generated upon heat treatment, mixed phases were also generated. However, the presence of organic molecules during the syntheses, as matrices, solvents or precipitating bases, had a profound effect upon the surface texture of the samples prepared.